Advocacy in authoritarian contexts: the case of disability NGOs in Russia. Issue 11 (3rd June 2020) - Toepler, Stefan; Fröhlich, Christian
Abstract : Purpose: The growing trend towards closing the political space for civil society in authoritarian regimes has primarily targeted NGOs focused on rights-based advocacy. Drawing on a study of disability NGOs in Russia, this paper seeks to contribute to a better understanding of the advocacy options that nonprofit organizations have even in repressive political contexts. The authors first review the extant literature to identify common actors, types and tactics and then trace what types of advocacy Russian NGOs are engaged in and what tactics they are able to utilize. Design/methodology/approach: The empirical part of this paper is based on 20 interviews conducted among active participants in disability NGOs in Moscow, St. Petersburg, Perm and Nizhniy Novgorod. Despite not being a representative sample of organizations, the selection of cities and organizations was intended to reflect spatial and structural factors of the field. Findings: The authors find that NGOs are able to pursue a broad range of advocacy activities despite a generally restrictive legal environment for civil society. Research limitations/implications: Research on advocacy in authoritarian countries is often focused on NGOs that are primarily engaged in these activities. This has overshadowed the considerable leeway that nonprofit service providers have to engage in advocacy. Practical implications: Service-providing NGOs should not forsake advocacy activities, even in authoritarian contexts, but can find access points in the political system and should seek to utilize their voice on behalf of their clients. Social implications: Despite general restrictions, NGOs can still find ways to successfully secure social rights, justice and solidarity, provided they accept the supremacy of the state in social policy and appeal to the state's responsibility for the welfare of its citizens without directly questioning the overall status quo too heavily. Originality/value: We develop a broad framework for various advocacy forms and activities and apply it to nonprofit service providers.